Dietary diversity modifies the association between household solid fuel use and sleep health in older adults - Ma, Xinyan; Zhao, Hanqing; Wang, Yan; Zhao, Yuhong; Zhou, Daan; Sun, Minghui (Frontiers in Nutrition, 2026)
BackgroundSleep health was crucial for healthy aging, yet it can be influenced by environmental factors and dietary habits. Evidence linking between cooking fuel use, dietary diversity, and sleep health, however, remains limited. This study aimed to investigate the aforementioned associations and to further assess the potential moderating role of dietary diversity.MethodsWe included 9,121 adults aged ≥65 years from the Chinese Longitudinal Healthy Longevity Survey (CLHLS). Information on household fuel use and sleep health were collected by validated questionnaires, and dietary diversity was assessed with a simplified food frequency questionnaire. We used logistic regression models to examine the associations of solid cooking fuel use and dietary diversity with sleep health.ResultsAmong the 9,121 participants included in the study, 4,848 (53.15%) reported good self-reported sleep quality and 3,324 (36.44%) reported adequate sleep duration. Exposure to solid cooking fuels was associated with poor self-reported sleep quality (odds ratio [OR] = 0.86; 95% confidence interval [CI] = 0.78–0.95). In contrast, a higher dietary diversity score (DDS) was associated with better self-reported sleep quality (OR = 1.50; 95%CI = 1.37–1.64) and adequate sleep duration (OR = 1.18; 95%CI = 1.07–1.30). Similarly, a higher anti-inflammatory dietary diversity score (AIDDS) showed significant associations with better self-reported sleep quality (OR = 1.53; 95%CI = 1.39–1.67) and adequate sleep duration (OR = 1.22; 95%CI = 1.11–1.34). Notably, participants with combined exposure to clean cooking fuels and a high DDS/AIDDS had substantially greater odds of better self-reported sleep quality and adequate sleep duration than those exposed to solid fuels with a low DDS/AIDDS (P for interaction < 0.05).ConclusionOur study indicates that exposure to solid cooking fuels was associated with poor self-reported sleep quality among older adults. Furthermore, higher dietary diversity may attenuate this adverse association, suggesting it is a promising target for public health interventions.